Deskripsi Antisipatori Remaja di Panti Asuhan Al-Washliyah - Putra, M. Harwansyah; Hasibuan, Irma Diani; Rezeki, Leni Sri; Sahdiah, Nur; Azhari, Putri Novi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Its purpose research was to decide the anticipatory level determined inside the Al-Washliyah orphanage. In this study, qualitative and quantitative approach or a mixed method. The reason for using this how to better understand your research question disclosing quantitative data in numerical form and qualitative data in descriptive form . The technique used in this study was a package containing written questions and interviews in the form of a number of questions asked directly to adolescents at the Al-Washliyah orphanage. Data analysis with quantitative descriptive and quantitative descriptive techniques. Qualitative descriptive was used to analyze the interview results while quantitative used to research the description consequences of the questionnaire.on this examine, the results obtained were that adolescents in the orphanage experienced moderate anticipatory conditions. Keywords: Anticipatory, Youth, Orphanage.